Factors determining effectiveness of e-learning in secondary schools - Palanisamy, Subramaniam; Ahlan, Abdul Rahman; Atanda, Balogun Naeem (IEEE, 2016)
This study explore factors to determine e-learning effectiveness in secondary school within Malaysia. The study used Technology Acceptance Model, Information Systems Success Model to propose a Model that can be used to determine effective use of e-learning in secondary school. The study is targeted at only secondary school students.